Pengaruh Penerapan Media Pembelajaran Interaktif Berbantu Assemblr Edu terhadap Hasil Belajar Aspek Kognitif pada Siswa Kelas IV MIS NU Palangka Raya: Effect of Implementing Interactive Learning Media Assisted by Assemblr Edu on Cognitive Aspect Learning Outcomes in Grade IV Students of MIS NU Palangka Raya - Jannah, Raudatul; Jasiah, Jasiah; Normuliati, Sri (Anterior Jurnal, 2025)
This study is based on the fact that the cognitive learning outcomes of fourth-grade students of MIS NU Palangka Raya in the subject of Science are still relatively low, especially the material "My Indonesia is Rich in Culture" related to local culture. This study aims to determine the effect of interactive learning media assisted by Assemblr Edu on the cognitive learning outcomes of MIS NU Palangka Raya fourth-grade students. A quantitative approach with a one-group pretest-posttest design was used in this study. The research subjects were 30 fourth-grade students of MIS NU Palangka Raya. The instruments used included multiple-choice tests, observation sheets, and documentation. The analysis results showed an increase in the average score from 47.00 in the pretest to 78.50 in the posttest. The Paired Sample t-Test obtained a significance value of 0.000 (<0.05), indicating a significant effect after implementing the media. In addition, the observation results showed that the implementation of the use of the media reached 93.75% in the first meeting and 95% in the second meeting, reflecting the active involvement of students in learning. Thus, the Assemblr Edu media influences students' cognitive learning outcomes in local culture-based science learning.